Normative construction of restorative justice implementation in accelerating state losses return in corruption crimes - Zahrulyani, Arip; Santoso, M. Iman; Maksum, Irfan Ridwan; Pratiwi, Siswantari (International Journal Labs, 2024)
The objective of this study is to explore the philosophical foundation for the application of restorative justice approaches in cases of corruption in Indonesia. The study aims to examine and analyze the success related to efforts to reclaim and take back state financial reimbursement due to corruption based on the provisions of Article 18 of Law Number 31 of 1999 concerning eradication of corruption crimes, which is mainly carried out by the process of confiscating the assets of the suspect's wealth which are found to have a relationship and link and match relationship with the suspect and his corruption crime. The research is intended to explore and discuss the shortcomings and challenges, both substantive and formal, in asset seizure for state recovery, as well as the analysis of the success of recovering substitute money in combating corruption crimes. Based on the research, it is concluded that the philosophy of Pancasila as a source of values derived from its five principles to guide the enforcement of law in Indonesia can be employed to examine Indonesian law.